2015
DOI: 10.1371/journal.pone.0145510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Facilitation of Local Stakeholder Groups on Equity in Neonatal Survival; Results from the NeoKIP Trial in Northern Vietnam

Abstract: BackgroundTo operationalize the post-MDG agenda, there is a need to evaluate the effects of health interventions on equity. The aim of this study is to evaluate the effect on equity in neonatal survival of the NeoKIP trial (ISRCTN44599712), a population-based, cluster-randomized intervention trial with facilitated local stakeholder groups for improved neonatal survival in Quang Ninh province in northern Vietnam.MethodsSemi-structured interviews were conducted with all mothers experiencing neonatal mortality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The interventions described in these articles fell into four broad types: home visits; community-based groups; cash transfers; mixed interventions involving multiple components, such as community meetings, media campaigns or community midwives. Some articles reported on the same interventions: four on participatory women’s groups in Northeast India,25–28 three on participatory women’s groups in Nepal26 27 29 and two on local stakeholder group interventions in Vietnam 30 31…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interventions described in these articles fell into four broad types: home visits; community-based groups; cash transfers; mixed interventions involving multiple components, such as community meetings, media campaigns or community midwives. Some articles reported on the same interventions: four on participatory women’s groups in Northeast India,25–28 three on participatory women’s groups in Nepal26 27 29 and two on local stakeholder group interventions in Vietnam 30 31…”
Section: Resultsmentioning
confidence: 99%
“…Two articles based on six randomised controlled trials of a women’s group intervention reported pro-equitable effects on neonatal mortality across socioeconomic groups (recorded once in figure 3). 27 28 One trial evaluating community stakeholder groups also reported a pro-poor improvement in NMR in intervention compared with control areas among wealth quintiles but not education or ethnicity groups 31. One study of a national community health programme (in figure 3 included under ‘Mixed interventions’) found that the density of CHWs in poor areas had no association with NMR, whereas in richer areas there was an association with higher neonatal mortality 42…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Vietnam, as well as in other Asian countries, intervention studies have shown that participatory approaches to community engagement can solve some of the local problems that threaten perinatal survival and thereby reduce neonatal mortality and increase equity in survival 30, 31, 32, 33. A number of organisations have played important roles in the child health revolutions in these countries, including the civil society and nongovernmental organisations in Bangladesh 23, the strong Women's Union in Vietnam 30 and communities that have engaged in development and welfare in Rwanda 6.…”
Section: Community Engagement and Child Survivalmentioning
confidence: 99%